Indocyanine Green Fluorescence Angiography During Laparoscopic Bariatric Surgery: A Pilot Study - Balla, Andrea; Corallino, Diletta; Quaresima, Silvia; Palmieri, Livia; Meoli, Francesca; Cordova Herencia, Ingrid; Paganini, Alessandro M. (Frontiers in Surgery, 2022)
Aims: Indocyanine green (ICG) fluorescence angiography (FA) is used for several purposes in general surgery, but its use in bariatric surgery is still debated. The objective of the present pilot study is to evaluate the intraoperative utility of ICG-FA during bariatric surgery in order to focus future research on a reliable tool to reduce the postoperative leak rate. Methods: Thirteen patients (4 men, 30.8%, 9 women, 69.2%) with median age of 52 years (confidence interval, CI 95% 46.2 - 58.7 years) and preoperative median body mass index of 42.6 kg/m2 (CI 95% 36 to 49.3 kg/m2) underwent bariatric surgery with ICG-FA in our center. Three mL of ICG diluted with 10 cc sterile water were intravenously injected after gastric tube creation during laparoscopic sleeve gastrectomy (LSG) and after the gastric pouch and gastro-jejunal anastomosis creation during laparoscopic gastric by-pass (LGB). For the ICG-FA, Karl Storz Image 1S D-Light system (Karl Storz Endoscope GmbH & C. K., Tuttlingen, Germany) placed at a fixed distance of 5 cm from the structures of interest and zoomed vision modality were used to identify the vascular supply. The perfusion pattern was assessed by the surgical team according to a score. The score ranged from 1 (poor vascularization) to 5 (excellent vascularization) based on the intensity and timing of fluorescence of the vascularized structures. Results: Fom January 2021 to February 2022, six patients underwent LSG (46.2%), three patients underwent LGB (23.1%), and four patients underwent re-do LGB after LSG (30.8%). No adverse effects to ICG were observed. In 11 patients (84.6%) ICG-FA score was 5. During two laparoscopic re-do LGB, the vascular supply was not satisfactory (score 2/5) and the surgical strategy was changed based on ICG-FA (15.4%). At a median follow-up of five months postoperatively, leaks did not occur in any case. Conclusions: ICG-FA during bariatric surgery is a safe, feasible and promising procedure. It could help to reduce the ischemic leak rate, even if standardization of the procedure and objective fluorescence quantification are still missing. Further prospective studies with a larger sample of patients are required to draw definitive conclusions.